2005
DOI: 10.1093/hmg/ddi365
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the homeobox gene Pitx2 in neural crest is required for optic stalk and ocular anterior segment development

Abstract: Heterozygous mutations in the homeobox gene, PITX2, result in ocular anterior segment defects and a high incidence of early-onset glaucoma. Pitx2 is expressed in both the neural crest and the mesoderm-derived precursors of the periocular mesenchyme. Complete loss of function in mice results in agenesis or severe disruption of periocular mesenchyme structures and extrinsic defects in early optic nerve development. However, the specific requirements for Pitx2 in neural crest versus mesoderm could not be determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 99 publications
7
173
0
Order By: Relevance
“…Our own studies have suggested that pitx2 regulates myogenic cell number cell autonomously, consistent with its ability to regulate cell proliferation in the satellite cell line, C2C12 (Kioussi et al, 2002;Francis-West, unpublished data). This has been confirmed recently by the demonstration that gene-inactivation of pitx2 in the periocular cranial neural crest cell does not affect the early differentiation of eye muscles (Evans and Gage, 2005).…”
Section: Molecular Biographies Of Developing Head Musclesmentioning
confidence: 75%
“…Our own studies have suggested that pitx2 regulates myogenic cell number cell autonomously, consistent with its ability to regulate cell proliferation in the satellite cell line, C2C12 (Kioussi et al, 2002;Francis-West, unpublished data). This has been confirmed recently by the demonstration that gene-inactivation of pitx2 in the periocular cranial neural crest cell does not affect the early differentiation of eye muscles (Evans and Gage, 2005).…”
Section: Molecular Biographies Of Developing Head Musclesmentioning
confidence: 75%
“…Pitx2 is strongly expressed in muscle (15), neural crest (20)(21)(22), cardiac fields (23) (C.K., unpublished data) and brain cell lineages (29). Mutants of the Pitx2 homeobox gene have phenotypes in body parts corresponding to each of the gene's embryonic expression domains.…”
Section: Discussionmentioning
confidence: 99%
“…These Pitx2 ϩ /myogenin Ϫ cells may be either surface ectoderm or neural crest derivatives. Pitx2 expression in neural crest derivatives has also been observed in other regions of the head (20)(21)(22)(23). Pitx2 expression was generally not observed in nonmyogenic territories surrounding anlagen in other regions of the body (17) Severe losses in myogenin ϩ /Pitx2 ϩ territories were observed in the region adjacent to the tongue that represents the vestigial jaw ( Fig.…”
Section: Pitx2 Is Required For Initiation Of Myogenic Progression In mentioning
confidence: 90%
“…2 This hypothesis is consistent with recent findings that PITX2 expression in neural crest cells is observed not only in the anterior segment but also in the vitreous cavity at embryonic day 12.5 in mice. 3 Moreover, the deletion of 6p25, on which FOXC1 is located, which has a functional link with PITX2, 4 was reported to be associated with PHPV and Axenfeld-Rieger syndrome, 5 a syndrome thought to present the same spectrum of defects as Peters' anomaly.…”
Section: Conflict Of Interestmentioning
confidence: 99%